Internalization of Tarbiyah Khuluqiyah for Children in Langgar Darut Taqwa Palajau Village - Rusdiana, Rusdiana; Fuady, Muhammad Noor; Basir, Abdul (J-PAI: Jurnal Pendidikan Agama Islam, 2024)
The purposes of this scientific article is to describe the meaning of Tarbiyah Khuluqiyah in the context of the Al-Quran and Hadith, Internalization of Tarbiyah Khuluqiyah in Daily Life in Children in Langgar Darut Taqwa Palajau Village analyze the challenges in internalizing these values in children at Palajau Village. This research method is field research and intersection four qualitative approach. The subjects of this research are 2 imams of Langgar Darut Taqwa. The object is the internalization of Tarbiyah Khuluqiyah of children in Langgar Darut Taqwa Palajau Village. Data collection of this study are observation, interviews and documentation. The research location is at the intersection of four Palajau Villages, Pandawan District, Hulu Sungai Tengah Regency, South Kalimantan Province. The results of this study are in the form of internalization of Tarbiyah Khuluqiyah in children at the intersection of four Palajau Villages which is carried out by carrying out various strategies, namely through exemplary, giving advice, mentoring, and giving rewards and punishments. Tarbiyah Khuluqiyah there has two challenges, namely due to the influence of socialization and social media. Tarbiyah Khuluqiyah also plays an important role in the formation of children with character which is reflected in several things, namely the formation of moral awareness, character development based on Tarbiyah Khuluqiyah values and social interaction. From these results, it can be concluded that the internalization of Tarbiyah Khuluqiyah for children in the Darut Taqwa langgar at intersection four Palajau is carried out by priests with various strategies and there are challenges